The Effect of Stocking Density on Survival and Growth of Tiger Shrimp (Penaeus monodon) Cultivated with Seaweed (Gracilaria sp.) in Traditional Pond - Sri Rejeki; Maulana Ibrahim; Dicky Harwanto (Journal Omni-Akuatika, 2025)
In order to overcome the decline of pond carrying capacity due to intensification, polyculture of Penaeus monodon with Gracilaria sp. can be implemented to allow sustainability. This study aimed  to evaluate the effect of shrimp densities in a polyculture system with Gracilaria sp. on the shrimp’s survival rate and growth. The research design used in this study was Randomized Block Design (RBD) in triplicate with 3 treatments of stocking density (2, 3, and 4 ind/m2). This research was carried out for 90 days in extensive ponds with 0% use of artificial feed. At the end of the study, the results showed that different stocking density applied had no significant effect (p>0.05) on growth performance. Nonetheless, shrimp at a stocking density of 2 ind/m2 had the highest survival rate (30.30±1.48%) compared to other treatments. Higher shrimp density causes competition for space, food, and oxygen which leads to stress resulting in suppressed growth of shrimp. However, Gracilaria integration in shrimp polyculture effectively reduces nutrient loads and stabilize water quality (temperature, pH, salinity, and DO), leading to improved shrimp health and a decreased need for chemical inputs, offering a practical, eco-friendly solution for maintaining shrimp growth in such a denser environment.Keywords: algae, aquaculture, bioremediation, coastal, integrated